The molecular mechanism for inhibiting the growth of nasopharyngeal carcinoma cells using polymethoxyflavonoids purified from pericarp of Citrus reticulata ‘Chachi’ via HSCCC - Yang, Wanling; Liang, Yiyao; Liu, Yujie; Chen, Baizhong; Wang, Kanghui; Chen, Xiaojing; Yu, Zhiqian; Yang, Depo; Cai, Yi; Zheng, Guodong (Frontiers in Pharmacology, 2023)
Polymethoxyflavonoids (PMFs), the main bioactive compounds naturally occurred in the pericarp of Citrus reticulata ‘Chachi’(CRCP), possess significant antitumor action. Whereas, the action of PMFs in nasopharyngeal carcinoma (NPC) is currently unknow. The present research was conducted to investigate the inhibitory of PMFs from CRCP on growth of NPC in vivo and vitro. In our research, high-speed counter-current chromatography (HSCCC) were used to separate four PMFs (nobiletin (NOB), 3,5,6,7,8,3’,4’-heptamethoxyflavone (HMF), tangeretin (TGN) and 5-hydroxy-6,7,8,3’,4’- pentamethoxyflavone (5-HPMF)) from CRCP. CCK-8 assay was applied for preliminary screening the cell viability of the above four PMFs. Moreover, Colony formation, Hoechst-33258 staining, transwell, and wound scratch assay were performed to access anti-proliferation, invasion, migration and apoptosis inducing ability of HMF on NPC-cells. NPC-tumors in xenograft tumor transplantation experiments were established to explore the effect of HMF (100 and 150 mg/kg/day) on NPC. The treated rats were used for observing histopathological changes by H&E staining and detecting Ki-67 by immunohistochemical technique. The expressions of P70S6K, p-P70S6K, S6, p-S6, COX-2, p53, and p-p53 were measured by Western blot. The four PMFs were obtained with high purity (over 95.0%). The results of preliminary screening by CCK-8 assay suggested HMF had the strongest inhibitory effect on NPC-cells' growth. Colony formation, Hoechst-33258 staining, transwell, and wound scratch assay indicated that HMF has significant anti-proliferation, invasion, migration and apoptosis inducing ability on NPC-cells. In addition, HMF suppressed the growth of NPC-tumors in xenograft tumor transplantation experiments. Further investigation suggested HMF regulated proliferation, apoptosis, migration, and invasion of NPC-cells through activating AMPK-dependent signaling pathways. In conclusion, HMF-induced AMPK activation inhibits the growth, invasion and metastatic potency of NPC-cells via a downregulation in the activation of the mTOR signaling pathway and COX-2 protein levels, as well as an enhancement in phosphorylation level of p53. Our studies provided crucial experimental basis for clinical treatment for NPC, and developing and utilizing PMFs from CRCP.